Faktor - Faktor yang Mempengaruhi Rendahnya Minat Wanita Usia Subur dalam Memilih Alat Kontrasepsi IUD di Desa Uring Kecamatan Pegasing Kabupaten Aceh TenggaraTahun 2022 - Siska Gustika; Deby Cyntia Yun; Anna Waris Nainggolan (STIKes Ibnu Sina Ajibarang, 2024)
Selected Effective Contraceptive Method (MKET) is a method of using contraception that is easy to obtain, effective in the long term, and does not cause inconvenience to the user. Acceptors must choose the selected type of effective contraception based on instructions from a doctor or midwife. Selected Effective Contraception Methods from: IUD (Intra Uterine Device), Birth Control Implant (Implant), and Steady Contraception (Vasectomy and Tubectomy). Meanwhile, non-MKET is a contraceptive device that has a relatively short period of action, consisting of condoms, pills and injections. Data analysis uses univariate, bivariate analysis. The results of this study show that what is significant is what factors influence the low interest of women of childbearing age in choosing IUD (Intra Uterine Device) contraception in Uring village, Pegasing subdistrict, Southeast Aceh district in 2022. Can be used as a source of information to mothers who will choose IUD (Intra Uterine Device) contraception in Uring village, Pegasing subdistrict, Southeast Aceh district in 2022.